Teachers' Attitudes toward the Usage of Mobile Devices in EFL Classroom - Ali Dogan* (European Journal of Educational Research, 2016)
Nowadays, technology is developing in a geometrically progressive manner. Its usage in different social areas is an imperative, rather than a choice. As expected, digital devices are applicable in the educational context, as well. Hence, the scope of the present study is to examine attitudes toward mobile learning among English teachers. For this purpose, we conducted a survey with 159 teachers from both state and private schools as well as universities in Turkey. In general, our results showed that teachers have positive attitudes toward the usage of mobile devices in the ESL learning context. However, there is an almost equal number of teachers who use and who do not use mobile devices and other digital contents in their classrooms. In addition, and according to teachers, there were two main obstacles to using mobile devices in teaching processes – lack of training and students' attitudes. On the other hand, the lowest ranked obstacles were school administrations and pedagogical justification.